2018
DOI: 10.1371/journal.pntd.0006674
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the value of surveillance data for improving model predictions of lymphatic filariasis elimination

Abstract: BackgroundMathematical models are increasingly being used to evaluate strategies aiming to achieve the control or elimination of parasitic diseases. Recently, owing to growing realization that process-oriented models are useful for ecological forecasts only if the biological processes are well defined, attention has focused on data assimilation as a means to improve the predictive performance of these models.Methodology and principal findingsWe report on the development of an analytical framework to quantify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 64 publications
2
11
0
Order By: Relevance
“…This suggests that the observed loss of information, while statistically relevant, may not be practically meaningful. This conclusion complements previous findings that predictive performance of LF models is improved by calibrating the model to baseline and monitoring data together [18]. In , for example, we show that data-informed models provide more precise predictions than unconstrained models and that it is valuable to also include post-intervention data in addition to baseline data to the model calibration procedure [18].…”
Section: Villagesupporting
confidence: 88%
See 3 more Smart Citations
“…This suggests that the observed loss of information, while statistically relevant, may not be practically meaningful. This conclusion complements previous findings that predictive performance of LF models is improved by calibrating the model to baseline and monitoring data together [18]. In , for example, we show that data-informed models provide more precise predictions than unconstrained models and that it is valuable to also include post-intervention data in addition to baseline data to the model calibration procedure [18].…”
Section: Villagesupporting
confidence: 88%
“…This constitutes a highly useful capability for disease management applications, since the discovery of information about pre-control prevalence in settings without such data is essential to policy makers for planning necessary interventions, determining the optimal frequency of monitoring activities, evaluating program progress, and applying for formal validation of elimination from the WHO [4,5,26,53]. This work has also provided additional insights regarding the value of data for refining parasite transmission models [13,[16][17][18]22]. We found that there was a loss of information (as measured by the Shannon information index) when we calibrated the model to mid-MDA data and hindcasted the initial conditions as opposed to fitting the model directly to baseline data.…”
Section: Villagementioning
confidence: 99%
See 2 more Smart Citations
“…The above conclusions are clearly conditioned on the ability of our modelling framework to reliably capture the dominant transmission dynamics of S. neavei -transmitted onchocerciasis in an endemic focus. While our BM-based modelling algorithm combines the advantageous features of mechanistic and statistical approaches to improve the estimation of local models for facilitating forecasts of interventions applied under a variety of field conditions, it is dependent, as for any data-driven predictive system, on the model structure employed, estimation procedure, and on the data used for facilitating model discovery 16,17 . Although our BM framework primarily focused attention on addressing parameter uncertainty with data, we note here firstly that the present model is based on previously established population models of onchocerciasis transmission 7,47 , with appropriate structural extensions made with regard to population-averaged mf uptake and larval development in the S. neavei vector host as well as the operation of different forms of host immunity in populations 48 .…”
Section: Discussionmentioning
confidence: 99%